ISOLATION, SCREENING AND CHARACTERIZATION OF ANTIBIOTIC PRODUCING ACTINOMYCETES FROM KAPULUPPADA PLASTIC WASTE DUMPING YARD, VISAKHAPATNAM - Duddu, Midhun Kumar; Guntuku, Girijasankar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To isolate, screen and characterize antibiotic producing actinomycetes from Kapuluppada plastic waste dumping yard, Visakhapatnam. Methods: A total of 12 soil samples were collected, serially diluted and spread on starch casein agar supplemented with Rifampicin and Cycloheximide for inhibition of bacteria and fungi, respectively. Cross-streak method was used to check the antagonistic activity of isolated actinomycetes against bacteria and fungi. Crude extracts from submerged state fermentation were used for the production of antimicrobial compounds. Agar well diffusion method was used for antimicrobial activity of crude extracts against test organisms. The isolates were characterized by morphological, physiological and biochemical methods. Results: A total of 110 actinomycete isolates were isolated from plastic waste dumping yard. All isolates had shown antimicrobial activity against one or more tested bacteria/fungi. The crude extract of the isolates PD66 (12.2 mm), PD85 (11.5 mm) were most active against methicillin-resistant Staphylococcus aureus, PD4 (14.1 mm), PD66 (15.6 mm) were active against Pseudomonas aeruginosa, whereas the extracts of PD10 (19.2 mm), PD47 (19.8 mm), PD106 (19.1 mm) were active against Candida albicans, PD10 (14.6 mm), PD82 (15.7 mm) active against Saccharomyces cereviciae. The isolates had shown varying morphological, physiological and biochemical characteristics. Conclusion: The actinomycetes isolated from Kapuluppada plastic waste dumping yard were found to be most promising microorganisms for the production of antibacterial and antifungal antibiotics. Â